(untitled) (Global Journal of Human-Social Science, 2020)
Economic growth has improved economic opportunities for women and men. However, widespread inequalities in developing countries including Vietnam exist between women and men with regards to their respective opportunities to influence and participate in activities within their society and to benefit from its resources. Due to their traditional gender roles, women are constrained in terms of time, energy since they have had the responsibility for meeting the demand of their family’s basic need, such as freshwater, food, and sanitation. Moreover, women can be regarded as the primary beneficiaries of water supply projects as well as are active in water supply policymaking, planning and implementation processes. This article investigates which roles women play in the project stages of rural water supply; and why they are often excluded from participation and management activities through water projects. The article recommends that more attention be given to gender analysis to guide water supply policy development in the region.